Project for Universal Management of Airways – part 1: concept and methods. (9th November 2020) - Chrimes, N.; Higgs, A.; Law, J. A.; Baker, P. A.; Cooper, R. M.; Greif, R.; Kovacs, G.; Myatra, S. N.; O'Sullivan, E. P.; Rosenblatt, W. H.; Ross, C. H.; Sakles, J. C.; et al.
Summary: Multiple professional groups and societies worldwide have produced airway management guidelines. These are typically targeted at the process of tracheal intubation by a particular provider group in a restricted category of patients and reflect practice preferences in a particular geographical region. The existence of multiple distinct guidelines for some (but not other) closely related circumstances, increases complexity and may obscure the underlying principles that are common to all of them. This has the potential to increase cognitive load; promote the grouping of ideas in silos; impair teamwork; and ultimately compromise patient care. Development of a single set of airway management guidelines that can be applied across and beyond these domains may improve implementation; promote standardisation; and facilitate collaboration between airway practitioners from diverse backgrounds. A global multidisciplinary group of both airway operators and assistants was assembled. Over a 3‐year period, a review of the existing airway guidelines and multiple reviews of the primary literature were combined with a structured process for determining expert consensus. Any discrepancies between these were analysed and reconciled. Where evidence in the literature was lacking, recommendations were made by expert consensus. Using the above process, a set of evidence‐based airway management guidelines was developed in consultation with airway practitioners from a broad spectrum of disciplines and geographical locations. While consistent with the recommendations of the existing English language guidelines, these universal guidelines also incorporate the most recent concepts in airway management as well as statements on areas not widely addressed by the existing guidelines. The recommendations will be published in four parts that respectively address: airway evaluation; airway strategy; airway rescue and communication of airway outcomes. Together, these universal guidelines will provide a single, comprehensive approach to airway management that can be consistently applied by airway practitioners globally, independent of their clinical background or the circumstances in which airway management occurs.